Emotion recognition using EEG signal and deep learning approach - Islam, Sayedi Hassan Bin; Mehdi, Md. Quamar; Rohan, Bhuiyan Yash; Mahmood, Syed Atif Imtiaz (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.